Enhancing tissue integration and angiogenesis of a novel nanocomposite polymer using plasma surface polymerisation, an in vitro and in vivo study. (16th October 2015) - Griffin, Michelle F.; Palgrave, Robert G.; Seifalian, Alexander M.; Butler, Peter E.; Kalaskar, Deepak M.
Abstract : Enhancing tissue integration and angiogenesis of a novel nanocomposite polymer using plasma surface modification, an in vitro and in vivo study. Abstract : Current surgical reconstruction of facial defects including nose or ear involves harvesting patient's own autologous tissue, causing donor site morbidity and is limited by tissue availability. The use of alternative synthetic materials is also limited due to complications related to poor tissue integration and angiogenesis, which lead to extrusion of implants and infection. We intend to meet this clinical challenge by using a novel nanocomposite called polyhedral oligomeric silsesquioxane poly(carbonate-urea)urethane (POSS-PCU), which has already been successfully taken to the clinical bench-side as a replacement for trachea, tear duct and vascular by-pass graft. In this study, we aimed to enhance tissue integration and angiogenesis of POSS-PCU using an established surface treatment technique, plasma surface polymerisation (PSP), functionalising the surface using NH2 and COOH chemical groups. Physical characterisation of scaffolds was achieved by using a number of techniques, including water contact angle, SEM, AFM and XPS to study the effects of PSM modification on the POSS-PCU nanocomposite in detail, which has not been previously documented. Wettability evaluation confirmed that scaffolds become hydrophilic and AFM analysis confirmed that nano topographical alterations resulted as a consequence of PSP treatment. Chemical functionalisation was confirmed using XPS, which suggested the presence of NH2 and COOH functional groups on the scaffolds. The modified scaffolds were then tested both in vitro and in vivo to investigate the potential of PSP modified POSS-PCU scaffolds on tissue integration and angiogenesis. In vitro analysis confirmed that PSM modification resulted in higher cellular growth, proliferation and ECM production as assessed by biochemical assays and immunofluorescence. Subcutaneous implantation of modified POSS-PCU scaffolds was then carried out over 12-weeks, resulting in enhanced tissue integration and angiogenesis ( p < 0.05). This study demonstrates a simple and cost effective surface modification method to overcome the current challenge of implant extrusion and infection caused by poor integration and angiogenesis.